Potential Immunomodulatory effect of Allium sativum oil and its major component allicin in the disease process of type 1 diabetic rats / Fatma Ali Alashkham - Alashkham, Fatma Ali (2014)
Diabetes mellitus is one of the most common endocrine disorders accompanied by many metabolic syndromes. Many studies have examined the hypoglycaemic effect of Allium sativum oil and its major component allicin in both types of diabetes mellitus, but till now the mechanism has not been discussed regarding type 1 diabetes mellitus (T1DM). The objectives of this study were to determine the potential immunomodulatory effect of the administration of Allium sativum oil and its major compound allicin in the disease process of T1DM by assessing the levels of anti- islet cell antibodies, Pan T lymphocytes marker (CD90), Pan B lymphocytes markers (CD19), Pan innate cells marker (CDllb) and serum insulin. Method: Male Sprague-Dawley rats with Streptozocin (STZ)-induced T1DM were used. T1DM induced to overnight fasted rats by intraperitoneal injection with a single dose of STZ 65mg/kg body weight. The six groups (6 rats in each group) under study received different doses of Allium sativum oil and allicin. Blood glucose levels were tested every morning (at 8 am) through 30 days of the experimental period. At the end of the experiment, and after completion of the experimental protocols, blood samples were collected from overnight fasting rats by cardiac puncture under anesthesia. Serum was assayed for anti- islet cell antibodies, Pan T lymphocyte marker (CD90), Pan B lymphocyte markers (CD 19), Pan innate cells marker (CD1 lb) and serum insulin using enzyme-linked immunosorbent assay (ELISA). Pancreatic tissues were taken from the rats for histology and they were fixed in 10%neutral formalin solution, Results: The results were compared to the ones obtained from healthy and non treated diabetic rats. The diabetic rats exhibited consistent hyperglycaemia and increased level of T, B lymphocytes markers, innate cells marker, and anti islet cells antibodies (ICA). There was a decrease in the serum insulin concentrations. Meanwhile administration of Allium sativum oil and allicin especially at high doses to the T1DM rats leads to significant decreases in the levels of all immunological parameters and increased semm insulin level. Conclusions: From this experiment it was observed Allium sativum oil and its major compound allicin exhibited immunomodulatory effect against autoimmune reactions in T1DM. The data provide new strategies for using Allium sativum and allicinto be recommended in the clinical management, control, and prevention of T1DM. In addition, our study suggested the possibility of using Allium sativum oil and allicin in the management of other autoimmune diseases.